Repositioning BPK as a One Gate System for Determining State Losses: A Study of the Constitutional Court's Decision in 2026 - Sulistyowati Sulistyowati; Gusti Bintang Maharaja; Siti Fatia Nazela (Siber International Journal of Advanced Law (SIJAL), 2026)
The determination of state losses in corruption cases in Indonesia has historically been a major source of legal uncertainty. This is due to multiple interpretations of authority between audit institutions and law enforcement officials, which often lead to jurisprudential clashes. The Constitutional Court Decision Number 28/PUU-XXIV/2026, handed down in early March 2026, is here to redefine the investigative audit architecture fundamentally. Through this ruling, the Constitutional Court established the Financial Audit Agency (BPK) as the sole authority to calculate, validate, and declare state financial losses in every corruption case. This doctrine is known as the one-gate system. This journal critically examines the BPK's repositioning by analyzing the philosophical foundations of the constitution, the juridical anatomy of the decision, and the paradigmatic consequences for the judicial system and the government bureaucracy. Through a normative juridical analysis supported by an institutional sociological approach, it was found that this decision confirmed corruption as an absolute material crime. In other words, state losses must be actual and real, not just potential. This decision also restores the function of criminal law as the ultimate remedy after administrative mechanisms, such as Claims for Damages, are exhausted. But on the other hand, the monopoly of the interpretation of state losses by one institution actually gives birth to a serious threat in the form of the erosion of the judge's epistemic authority in the courtroom. Judges risk being reduced to a mere stamp of legitimacy for audit figures fabricated outside the judicial system. In addition, the BPK's institutionally limited capacity creates a bottleneck effect, stalling thousands of corruption cases as they await audit results. This study recommends a limited revision of the Law on the Eradication of Corruption Crimes. The revision should not focus on the struggle for the institution's stamp but on establishing a standard methodology for calculating state losses that applies nationally, openly, and accountably. With clear standards, any technical entity can perform the calculations, and the judge again holds sovereignty over the final judgment.